SCRATCH – Programming environment in inclusive education features of application in the practice of project-oriented learning (Journal of Educational Sciences, 2024)
Digital literacy plays a key role in the formation of an inclusive educational space that can adapt to the unique needs of each student, ensuring equal access to education. As a result of teaching the subject "Informatics" in general education schools, there are no specific examples of projects and pedagogical methods successfully used in inclusive education through computer programs, for example, using Scratch. That is, there is a need for special children to develop computing skills, thinking with the help of software tools. In this regard, the research work aimed to identify the specifics of learning using the Scratch environment of the project–oriented method of teaching in inclusive classrooms. To achieve this goal, the conditions were first identified and the experience of the project method of teaching secondary schools at the republican level was analyzed. Secondly, a curriculum of project tasks that form students' system thinking has been developed, compiled in a Scratch programming environment. The effectiveness of the project-oriented teaching method is determined and the ways of practical implementation are introduced through the optional class "Programming in the Scratch environment" according to the developed curriculum.In addition to the proposed course curriculum, an educational and methodological collection of practical tasks "creating a project in a Scratch environment" has been developed and introduced into the educational process, and the effectiveness of the proposed teaching methods has been determined as a result of the experiment.Key words: Inclusive environment, project-oriented learning, Scratch programming environment, computer science, digital literacy, teaching methods, special educational needs.